OPEN DEFECATION IN BURKINA FASO: A BOX-JENKINS ARIMA APPROACH (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Employing annual time series data on the number of people who practice open defecation in Burkina Faso from 2000 – 2017, the study predicts the annual number of people who will still be practicing open defecation over the period 2018 – 2022. The study applies the Box-Jenkins ARIMA method. The diagnostic ADF tests show that the series under consideration is an I (1) variable. Based on the AIC, the study presents the ARIMA (2, 1, 0) model as the optimal model. The diagnostic tests further reveal that the presented model is very stable and its residuals are not only stationary in levels but also normally distributed. The results of the study indicate that the number of people practicing open defecation in Burkina Faso is still very high although it is likely to decline over the period 2018 – 2022, from 44.81% to 39.28% of the total population. The study suggested the following: [i] the government of Burkina Faso should continue to make toilets a status symbol so that people consider toilets to be “rooms of happiness”. [ii] the government of Burkina Faso should create more demand for sanitation. There is need for the government of Burkina Faso to effectively deliver Water Supply and Sanitation programs at all levels. This can only happen if there is peace and security in the country. Political instability, has, over the years, delayed progress towards total sanitation and hygiene in Burkina Faso. [iii] there is need for the government of Burkina Faso to encourage a habit of systematic hand-washing, and not defecating in the open.